2021
DOI: 10.1159/000512383
|View full text |Cite
|
Sign up to set email alerts
|

Computer Vision-Based Assessment of Motor Functioning in Schizophrenia: Use of Smartphones for Remote Measurement of Schizophrenia Symptomatology

Abstract: <b><i>Introduction:</i></b> Motor abnormalities have been shown to be a distinct component of schizophrenia symptomatology. However, objective and scalable methods for assessment of motor functioning in schizophrenia are lacking. Advancements in machine learning-based digital tools have allowed for automated and remote “digital phenotyping” of disease symptomatology. Here, we assess the performance of a computer vision-based assessment of motor functioning as a characteristic of schizop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 56 publications
1
31
0
Order By: Relevance
“…In recent years, in the research on the analysis of abnormal speech (Holmlund et al, 2020 ; Tang et al, 2021 ) and head movement (Robson et al, 2016 ; Abbas et al, 2021 ) of schizophrenia, the sample number of schizophrenic patients is about 20: Tang et al ( 2021 ) use the dataset of 20 patients vs. 11 controls; Holmlund et al ( 2020 ) use the dataset of 25 patients vs. 79 controls; Abbas et al ( 2021 ) use the dataset of 18 patients vs. 9 controls; Robson et al ( 2016 ) use the dataset of 23 patients vs. 23 controls.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, in the research on the analysis of abnormal speech (Holmlund et al, 2020 ; Tang et al, 2021 ) and head movement (Robson et al, 2016 ; Abbas et al, 2021 ) of schizophrenia, the sample number of schizophrenic patients is about 20: Tang et al ( 2021 ) use the dataset of 20 patients vs. 11 controls; Holmlund et al ( 2020 ) use the dataset of 25 patients vs. 79 controls; Abbas et al ( 2021 ) use the dataset of 18 patients vs. 9 controls; Robson et al ( 2016 ) use the dataset of 23 patients vs. 23 controls.…”
Section: Methodsmentioning
confidence: 99%
“…Head movement is mainly body movement when reading the specified text in a fixed position. Studies have reported that schizophrenic patients have significant differences in head movement rates from controls (Abbas et al, 2021 ), and produce unconscious and unnecessary head movement in visual tasks (Yoo et al, 2005 ). The head movement measuring methods used in the present research include motion energy analysis (MEA) (Kupper et al, 2010 , 2015 ) and head-mounted motion sensors (Leask et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…This software platform has historically been used in clinical research for reporting of patient behavior to clinicians, including medication adherence, electronic patient-reported outcomes, and ecological momentary assessments, with considerable work done on patient acceptance and usability ( 32 , 33 ). An additional functionality of capturing video and audio in response to prompts (as described below) was utilized for the purposes of this study ( 34 , 35 ).…”
Section: Methodsmentioning
confidence: 99%
“…Montgomery-Åsberg Depression Rating Scale: The MADRS is a 10-item clinician administered scale for the measurement of MDD with validated clinical cut points for severe (>34), moderate (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34), mild (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19), and asymptomatic (<7) depression. The MADRS has demonstrated validity as a sensitive measure of ADT response (31).…”
Section: Assessments Clinical Assessmentmentioning
confidence: 99%
“…Although body language and facial expressions form a key part of a psychiatric exam, ML has only recently been applied to analyze such data objectively. To date, most work has been targeted to support the care for suicidal ideation [187] and depression [165], [166], [188], with few studies also dedicated to schizophrenia [175] and autism spectrum disorders [189]. Features derived from video data have been found to be relevant across all of these disorders.…”
Section: Speech and Video Analysesmentioning
confidence: 99%